Questioning the Legitimacy of the View that Zakat is Different from Tax (Historical Analysis) - Yosa Wananda; Jamal Abdul Aziz (JURNAL PENDIDIKAN IPS, 2025)
This article examines historically and conceptually the view that separates zakat and taxes in Islamic legal discourse. Zakat is an obligation that has great potential for welfare and benefit, which are the objectives of sharia (Maqāṣid al-sharī‘ah). Using a qualitative-historical approach and discourse analysis, this study explores how the relationship between zakat and taxes is formed, maintained, and reproduced in various political and social contexts of the Muslim community. In the early days of Islam, zakat functioned as the primary fiscal instrument of the state based on revelation. However, during the Abbasid period, the emergence of complex fiscal needs prompted the institutionalization of additional taxes outside the zakat framework. The view that zakat ≠ tax became stronger during the colonial era, when modern taxation was imposed by secular powers and zakat was maintained as a symbol of religious identity. In the context of a modern state like Indonesia, this view remains dominant in regulations and social practices, despite the emergence of various integrative discourses. This study concludes that the separation between zakat and taxes is more of a historical and ideological construction than an absolute sharia norm. Therefore, a more contextual Islamic legal approach based on maqāṣid al-syarī‘ah is needed to formulate the ideal relationship between zakat and taxes in the fiscal system of contemporary Muslim countries.